Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $f\colon [a,b] \to \mathbb{R}$ is continuous and has a finite derivative $f'$ everywhere on $(a,b)$.

If $f(a)=f(b)=0$ prove that for every $y\in\mathbb{R}$ there is some $c$ in $(a,b)$ with $f'(c) = yf(c)$.

We were given a hint to apply Rolle's theorem to $h(x)f(x)$ for an $h$ that depends on $y$ but I don't understand how to apply Rolle's theorem here.

share|cite|improve this question
Please consider using LaTeX mark-up and punctutation in your posts. – Arturo Magidin Nov 23 '10 at 20:44
Is h(x) the same as g? – Ross Millikan Nov 23 '10 at 20:46
@Ross Millikan, @JimJones: almost certainly, but it was like this in the original; I only LaTeX-ed it. I'll fix that. – Arturo Magidin Nov 23 '10 at 20:50
up vote 2 down vote accepted


Given $y \in \mathbb{R}$, consider the function $g_y(x)$ as below.

$g_y(x) = e^{-yx} f(x)$.

Apply Rolle's to $g_y(x)$.

(In general, if you find equations where the derivative is proportional to the function as in this case where $f'(c) \propto f(c)$, the detective in you must suspect immediately that the exponential function must be there somewhere in the picture)

share|cite|improve this answer

Suppose you have a function $h(x)$ which is differentiable, and you consider the function $\mathcal{F}(x) = h(x)f(x)$.

Since $h$ and $f$ are both continuous on $[a,b]$, so is $\mathcal{F}$.

Since $h$ and $f$ are both differentiable on $(a,b)$, so is $\mathcal{F}$.

Since $f(a)=f(b)=0$, then $\mathcal{F}(a)=h(a)f(a)=0$ and $\mathcal{F}(b)=h(b)f(b)=0$, regardless of what $h(x)$ is.

So, $\mathcal{F}$ will also satisfy Rolle's Theorem, and so you know that there exists $c\in (a,b)$ such that $\mathcal{F}'(c)=0$.

Now, what is $\mathcal{F}'(c)$? Well, $$\mathcal{F}'(x) = h'(x)f(x) + h(x)f'(x).$$ So $\mathcal{F}'(c) = h'(c)f(c) + h(c)f'(c)$. You want $f'(c)=yf(c)$, so you want $$ 0 = h'(c)f(c) + h(c)f'(c) = h'(c)f(c) + h(c)yf(c) = f(c)\Bigl(h'(c)+yh(c)\Bigr).$$ So either $f(c)=0$, or else $h'(c)+yh(c)=0$. You don't want $f(c)=0$ unless $y=0$, so in general you just want $h'(c)+yh(c)=0$.

How about trying to find some function $h(x)$ such that $h'(x) = -yh(x)$ for all $x$? Then use that for $\mathcal{F}$. Obviously, your choice of $h$ will depend on $y$.

share|cite|improve this answer
$h'(x) = -yh(x)$, $\forall x$ – user17762 Nov 23 '10 at 20:51
@Sivaram: Thanks! – Arturo Magidin Nov 23 '10 at 20:52

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.